1978
DOI: 10.1007/bf00584238
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in the mesentery microcirculation between normotensive and spontaneously hypertensive rats

Abstract: The mesentery preparation of normotensive rats (NR) (Pcarotis97 +/- 4 mm Hg) and of spontaneously hypertensive rats (SHR) (161 +/- 2 mm Hg) of comparable age (20 +/- 3 weeks) was used to study morphological changes of the microvasculature in established hypertension. The arterioles, classified according to their branching order, had an increased inner diameter in SHR (by 20%). The smooth muscle hypertrophy decreased with smaller vessel size. Pre- and postcapillary vessels were shorter in SHR than in NR by 17 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…Thus the high salt diet exaggerated a pattern al ready present in standard salt SHR. Our re sults showing not significantly different me dia/lumen area ratios between SHR and WKY in the smallest arteriolar category are consistent with those of Henrich et al [1978] on the mature in vivo mesenteric vascular bed. These investigators showed a gradually disappearing difference in relative wall thick ness between SHR and WKY with decreasing size arterioles.…”
Section: Discussionsupporting
confidence: 76%
“…Thus the high salt diet exaggerated a pattern al ready present in standard salt SHR. Our re sults showing not significantly different me dia/lumen area ratios between SHR and WKY in the smallest arteriolar category are consistent with those of Henrich et al [1978] on the mature in vivo mesenteric vascular bed. These investigators showed a gradually disappearing difference in relative wall thick ness between SHR and WKY with decreasing size arterioles.…”
Section: Discussionsupporting
confidence: 76%
“…measured directly by microscopy, it appears that the lumen diameter and media thickness of resistance vessels with lumen diameters of less than 100 pm are essentially the same as for those in WKYs, but that the number of resistance vessels is reduced [Henrich et al, 1978]. In more extensive studies on the vascular bed of the cremaster muscle a similar rarefication [Hutchins and Darnell.…”
Section: Vascular Constriction or Vascular Rarefication?mentioning
confidence: 70%
“…Studies have reported microvascular structural rarefaction in many experimental hypertensive models and tissues, including skeletal muscle, 18,30 -33 intestine, 34 and skin, 35 although not the brain. 36 Interestingly, structural rarefaction can be detected at a very young age (4 weeks) in spontaneously hypertensive rats.…”
Section: Experimental Datamentioning
confidence: 99%